Rewriting P Systems with Conditional Communication: Improved Hierarchies - Ramesh, H.; Rama, Raghavan (Computing and Informatics, 2012)
We consider here a variant of rewriting P systems [1], where communication is controlled by the contents of the strings, not by the evolution rules used for obtaining these strings. Some new characterizations of recursively enumerable languages are obtained by means of P systems with a small number of membranes, which improves some of the known results from [1] and [4].